Disruptive emerging transportation technologies - Wei, Heng (Civil engineer); Wang, Yinhai; Ma, Jianming (Engineer) (American Society of Civil Engineers, 2022)
"This title provides a forward-looking overview of the relevant 4IR technologies and their potential impacts on the future disruptive emerging transportation"-- Provided by publisher
Keywords: Transportation -- Technological innovations.; Traffic engineering -- Technological innovations.; Industry 4.0.; elektronické knihy; electronic books